Cardiovascular adverse events associated with antibody-drug conjugates (ADCs): a pharmacovigilance study based on the FAERS database - Long, PingPing; Li, Siyu; Pan, Lingyun; Wang, Yuanqiang; Chen, Wanyi; Wang, Xiaoxiao (Frontiers in Pharmacology, 2024)
Objective: As a novel drug formulation, Antibody-drug conjugates (ADCs) are widely used in various types of cancer. However, clinically, there is a lack of attention to the CVD produced by them, as well as a lack of research on the real-world situation. Using the Food and Drug Administration Adverse Event Reporting System (FAERS) database, to ensure its clinical safety application, we analyzed post-marketing data on antitumor ADCs to identify risk factors and drugs associated with the risk of cardiovascular events. cases were associated with polatuzumab vedotin, 62 ( 29% ) with trastuzumab deruxtecan, 423 ( 54.3% ) with gemtuzumab ozogamicin, and 66 ( 38.8% ) with inotuzumab ozogamicin. In a disproportionate number of SMQS, cardiac failure (n = 277) and embolic and thrombotic events, venous (n =446) were the most frequently reported CVD-related AEs in ADCs.Conclusions：By mining the FAERS database, we provided relevant information on the association between ADC use and cardiovascular-associated AEs. ADCs were associated with increased cardiovascular toxicity, deserving distinct monitoring and appropriate management. Further research is needed to confirm these findings and assess causality.